IT Governance Capability Analysis in Digital Service Improvement at Pizza Hut Sunset Point: COBIT 5 Approach - Winarko, Triyugo; Bakri, Asri Ady; Susanto, Edy; Sumartono, Sumartono (PT.KARYA GEMAH RIPAH, 2024)
The development of digitization makes the success of an organization is greatly influenced by the ability to manage information technology (IT) to improve digital services. Pizza Hut Sunset Point faces great challenges in ensuring that their IT systems are able to support optimal service. This study aims to measure IT governance capability at Pizza Hut Sunset Point using the COBIT 5 framework and identify areas that require improvement to improve digital services. The methods used include surveys and GAP analysis to assess the maturity level of various COBIT 5 domains, including EDM, APO, BAI, DSS, and MEA. The results show that although some domains such as BAI and some EDM have reached the maturity target, there are still some domains that require improvement, especially DSS and MEA. Recommendations for improvement include improving performance measurement metrics, strengthening IT strategy, and regularly evaluating vendors and IT partners. With the implementation of these recommendations, it is expected that Pizza Hut Sunset Point can improve their IT governance capabilities, thereby supporting more efficient digital services and increasing customer satisfaction. This research provides practical guidance for management to improve IT governance and develop effective digital strategies in the F&B industry.